Mitigation of Simpai (Presbitys melalophos) Disturbance on Agroforestry in Protection Forest Register 25 Pematang Tanggang, Kelumbayan, Tanggamus - Nasichah, Zulfatun; Harianto, Sugeng Prayitno; Winarno, Gunardi Djoko (Jurnal Sylva Lestari, 2018)
One of the contents within the Government Regulation Number 6 Year 2007 is regulating permissions on how communities can sustainably utilize forest land exclude in protection blocks, for instance agroforestry. Disturbance by wildlife as simpai (Presbytis melalophos) is occurred in an agroforestry land located in the Protection Forest Register 25 Pematang Tanggang, Kelumbayan Tanggamus. The underlying repercussions from the disturbance particularly because agroforestry systems that managed by cummunities contains food sources of simpai such as juvenile leaves and fruits. The aims of this study were to analyze the intensity of disturbance based on activity range, type of crop, time of simpai activities and analyze the mitigation effort. Field observation and interview with communities were used as the research method. The results showed that the highest disturbance of simpai based on the activity range is on agroforestry area where feed resources are quite abundant. The type of plants that disturbed was mostly consisting of banana and cocoa. In addition, the intensity of encounter time predominantly at 5:00 to 7:45 am. Simpai was rarely seen in the afternoon and could be found again at 04:00 to 05:30 pm. The lack of the community knowledge on the conservation status of the wildlife has caused the practices of environmentally-aggressive control of simpai such as by trapping and even shooting. A more environmentally-friendly mitigation effort was performed through the protection of crop, for example by covering fruits before harvesting. Key words: agroforestry, Presbytis melalophos, mitigation, simpai.